Gender Through the Lens of Children’s Films - Woodsmall, ZoraAnn; Hare, Sara (Advances in Social Sciences Research Journal, 2022)
This content analysis study sheds light on the gender inequality in popular children’s animated films. The dataset uses the North American theater grosses to rank the most popular 150 animated children’s films from 1990-2020. We found multiple patterns of gender inequality related to speaking roles, lead characters, physical portrayals, social roles, interpersonal relationships, and even the creators of the films. Male characters had three times as many speaking roles as female characters and had the lead role in 80% of the films. Correspondingly, 80% of the film creators (writers, directors, and producers) were male. Films that passed the Bechdel test had twice as many female writers as those that failed the test. The inequality and gender stereotyping one sees in the real world is reflected in this study of children’s films. Animated films are a popular media outlet for children, and this study highlights the impact that these skewed representations can have on children.